ADMINISTRAÇÃO PÚBLICA E RESPONSABILIDADE SOCIAL E SUSTENTABILIDADE, COMPROMISSO DA INSTITUIÇÃO DE ENSINO PÚBLICA: UM ESTUDO DE CASO DO INSTITUTO FEDERAL FLUMINENSE - Freitas, Isabel Grigorio (2013)
This study has as I aim to identify improvements for adaptation of the actions resulting from the government social projects to the real necessities of the communities affected and attended by the public institutions of teaching from the understanding of the promise of these institutions with the social responsibility and the sustainable development and of the analysis of the main difficulties for implementation of social projects formatted by the federal government sphere that do not consider the peculiarities of several communities that are near the public installations. In the analysis of the social projects, the implemented ones according to received directives of the federal government receive bigger attention, using concept of social responsibility, the analysis of public policies turned to the education and the case study of the Instituto Federal de Educação, Ciência e Tecnologia Fluminense for bigger use and understanding of the data of the inquiry.